New England State Politics - Lockard, Duane (Princeton, NJ : Princeton University Press, 2015)
A down-to-earth and fact-filled discussion of New England state politics based on seven years of research and over 1,000 interviews.Originally published in 1959.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- PREFACE / L., W.D. -- CONTENTS -- CHAPTER 1. ABOUT NEW ENGLAND: AN INTRODUCTION -- CHAPTER 2. VERMONT: POLITICAL PARADOX -- CHAPTER 3. NEW HAMPSHIRE POLITICS: TRIUMPH OF CONSERVATISM -- CHAPTER 4. MAINE: PINE, POWER, AND POLITICS -- CHAPTER 5. MASSACHUSETTS: THE STANDING ORDER UNDER ATTACK -- CHAPTER 6. LAWMAKING IN MASSACHUSETTS: TRADITIONAL POMP AND POLITICAL CIRCUMSTANCE -- CHAPTER 7. RHODE ISLAND: ONE-PARTY FACADE AND TWO-PARTY REALITY? -- CHAPTER 8. RHODE ISLAND: POLITICS ON THE SEAMY SIDE -- CHAPTER 9. CONNECTICUT: THE POLITICS OF COMPETITION -- CHAPTER 10. CONNECTICUT: LEGISLATIVE POLITICS AND PARTY COMPETITION -- CHAPTER 11. ETHNIC ELEMENTS IN NEW ENGLAND POLITICS -- CHAPTER 12. PUBLIC POLICY-MAKING AND POLITICAL PARTIES IN NEW ENGLAND -- INDEX
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Political parties -- New England; 2 -- isacsh